A Case of IgG4-Related Kidney Disease Developing While on Steroid Treatment for Autoimmune IgG4 Pancreatitis. (June 2021) - Reyes, Jonathan Vincent M.; Maldonado, Dawn; Stern, Aaron S.; Brown, Maritza
IgG4 (immunoglobulin G4)-related systemic disease is an autoimmune process affecting multiple organ systems. This inflammatory process can present as but not limited to pancreatitis, cholangitis, or unspecified kidney disease. In this case, our patient developed IgG4-related kidney disease while already on a prolonged steroid course for IgG4-related pancreatitis. The patient ultimately had renal recovery after starting a higher dose of prednisone, but also developed steroid-related complications. This case further highlights the relationship between IgG4 diseases now termed IgG4-related systemic disease. This case brings to light the need for further investigative research into ideal steroid dosing, as well as steroid-sparing agents for IgG4-related systemic disease.